2007
DOI: 10.1016/j.nuclcard.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in myocardial oxygen and glucose metabolism

Abstract: Background-Both physiologic and pathophysiologic conditions affect the myocardium's substrate use and consequently, its structure, function, and adaptability. The effect of sex on myocardial oxygen, glucose, and fatty acid metabolism in humans is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 38 publications
5
57
1
Order By: Relevance
“…Peterson and colleagues (1,3) found that women had significantly higher myocardial oxidative metabolism compared with men, which may have explained increased myocardial NEFA uptake and oxidation. The latter observations were performed during fasting and may not necessarily apply to the postprandial state, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peterson and colleagues (1,3) found that women had significantly higher myocardial oxidative metabolism compared with men, which may have explained increased myocardial NEFA uptake and oxidation. The latter observations were performed during fasting and may not necessarily apply to the postprandial state, however.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the fasting state show that women have greater myocardial oxygen consumption (1), which increases with obesity (2). In addition, female sex appears to be an important predictor of higher diabetes-associated cardiac plasma nonesterified fatty acid (NEFA) utilization (3).…”
mentioning
confidence: 99%
“…If a treatment effect was found among the three groups, paired comparisons were used to evaluate the differences between any two groups' responses to therapy. Because of known sex effects on myocardial metabolism, we performed subgroup analyses of the treatment effects within each sex using paired t-tests (19,20 …”
Section: Methodsmentioning
confidence: 99%
“…Sex-related differences in myocardial flow, oxygen consumption, efficiency, and metabolism have also been observed in prior PET-related studies in healthy and obese subjects, patients with type 2 diabetes, and patients with nonischemic cardiomyopathy. [6][7][8] In several studies of healthy and obese individuals, women tended to have higher myocardial blood flow than men. [7][8][9] This is similar to the results from the current study by Duvernoy et al 5 Myocardial blood flow was also higher in women with type 2 diabetes compared with men with the same disease.…”
mentioning
confidence: 99%
“…[6][7][8] In several studies of healthy and obese individuals, women tended to have higher myocardial blood flow than men. [7][8][9] This is similar to the results from the current study by Duvernoy et al 5 Myocardial blood flow was also higher in women with type 2 diabetes compared with men with the same disease. This is consistent with prior literature, which has been fairly consistent in demonstrating that oxygen consumption is generally higher in womennormal, obese, and with type 2 diabetes mellitus, than in comparable groups of men.…”
mentioning
confidence: 99%